2019
DOI: 10.1177/1467358419863157
|View full text |Cite
|
Sign up to set email alerts
|

Back to basics: Academic research in tourism and hospitality management – The case of Hong Kong

Abstract: As universities compete for resources, research output has become more important and the key determinant in academic success. While much work has been done, it is limited to studying specific dimensions of research performance, with inherent methodological limitations such as the choice of journals to be included for examination, methods of counting, and research performance measures. This study takes a different route. Based on a constructivist grounded theory methodology, it explores the question of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the domain of tourism and hospitality, studies examining the meanings and characteristics of good research are scarce. Good research was illustrated by Chin such that research starts with an important inquiry and pushes the boundary further, on the basis of his investigation in six tourism universities of Hong Kong [33]. A few scholars started to explore the perspectives of important persons in evaluating research performance.…”
Section: Good Researchmentioning
confidence: 99%
“…In the domain of tourism and hospitality, studies examining the meanings and characteristics of good research are scarce. Good research was illustrated by Chin such that research starts with an important inquiry and pushes the boundary further, on the basis of his investigation in six tourism universities of Hong Kong [33]. A few scholars started to explore the perspectives of important persons in evaluating research performance.…”
Section: Good Researchmentioning
confidence: 99%
“…For example, using a knowledge management framework, Mody et al (2018) identified institutional factors that serve as antecedents of a supportive culture and effective infrastructure for nurturing impactful researchers. Also, Chin and Law (2020) adopted a constructivist approach to identify research habits for impactful scholarship by interviewing a sample of 36 researchers in Hong Kong. In addition, Phillips et al (2018) conducted a study to understand the impact of business issues on society from the perspective of practitioners, society and researchers.…”
Section: Introductionmentioning
confidence: 99%